Implementing the Montessori approach in an undergraduate marketing course: A case study - Murray, Angela K.; Miller, Michael; Postlewaite, Elyse L.; Clark, Kiara (Frontiers in Education, 2022)
The objective of this case study is to offer a new perspective on innovation in higher education pedagogy by exploring how Montessori principles can be applied in an elective upper-level undergraduate marketing analytics course. Innovation in higher education is crucial for preparing students for the ever-changing challenges they will face in the workplace and in society. Montessori education offers a unique perspective for addressing many of the shortcomings identified in current approaches to undergraduate instruction. This study involved designing a course that incorporated well-established principles of Montessori education—which has demonstrated success in fostering deep learning, engagement, intrinsic motivation, and adaptability particularly among adolescents. The methodology leverages the naturalistic approach to gathering real world evidence using an inductive design based on data from instructor field notes, weekly student response submissions, and an end-of-semester student survey. In conclusion, results of the study suggest Montessori education, particularly experiential learning elements and direct connections to industry, should continue to be explored for its potential to inspire innovation in higher education. However, successfully changing the instructional paradigm requires efforts beyond a single course. Truly shaping undergraduate education for the 21st Century involves broad and integrated change across departments and even universities to empower students to take control of their own learning, to be inspired and motivated by their own intrinsic values, and to expand their thinking beyond narrow expectations of textbook learning.